(untitled) (Revista horizonte, 2022)
The purpose of the research was to determine the relationship between enjoyment and the level of physical activity (PA) in students participating in health promotion programs. 298 students (50.6% male, 49.4% female) enrolled in the first year of careers taught by the Peruvian Union University and also enrolled in health promotion programs. The International Physical Activity Questionnaire (IPAQ) was applied to measure the level of physical activity and the Physical Activity Enjoyment Scale (PACE) to measure the enjoyment in PA. There is no correlation between the enjoyment of PA and weekly physical activity (r = 0.082; p = 0.158). Although, there is no correlation between the enjoyment and the weekly PA, the students who most enjoy performing PA, are the ones who have the best levels of PA (moderate and vigorous), which otherwise would be above the reality of Peru.